2015
DOI: 10.3174/ajnr.a4312
|View full text |Cite
|
Sign up to set email alerts
|

Tract-Based Spatial Statistics in Preterm-Born Neonates Predicts Cognitive and Motor Outcomes at 18 Months

Abstract: BACKGROUND AND PURPOSE:Adverse neurodevelopmental outcome is common in children born preterm. Early sensitive predictors of neurodevelopmental outcome such as MR imaging are needed. Tract-based spatial statistics, a diffusion MR imaging analysis method, performed at term-equivalent age (40 weeks) is a promising predictor of neurodevelopmental outcomes in children born very preterm. We sought to determine the association of tract-based spatial statistics findings before term-equivalent age with neurodevelopment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
56
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(62 citation statements)
references
References 28 publications
(33 reference statements)
3
56
2
Order By: Relevance
“…The TBSS FA data were projected onto a mean FA tract skeleton, which was used to apply the voxelwise cross-subject statistics 23. We used five age-based templates and were able to compare neonate groups with a standardised analysis and a calculated voxel significance threshold of p<0.05 adjusted for PMA at scan 12. White matter abnormalities detected with TBSS at term-equivalent age have been shown to predict neurodevelopmental outcomes in preterm neonates 12 24…”
Section: Methodsmentioning
confidence: 99%
“…The TBSS FA data were projected onto a mean FA tract skeleton, which was used to apply the voxelwise cross-subject statistics 23. We used five age-based templates and were able to compare neonate groups with a standardised analysis and a calculated voxel significance threshold of p<0.05 adjusted for PMA at scan 12. White matter abnormalities detected with TBSS at term-equivalent age have been shown to predict neurodevelopmental outcomes in preterm neonates 12 24…”
Section: Methodsmentioning
confidence: 99%
“…An alternative to the ROI approach is to analyse DTI data for the whole brain volume, which can detect more subtle brain injury (23). Previous studies that applied whole brain statistical analysis for DTI parameters in preterm infants demonstrated a reduction in DTI measures, thought to reflect alternations in brain microstructure (24, 25).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, few studies have been conducted to evaluate the correlations between WM connectivity as revealed by DTI and motor neurodevelopment of extremely low birth weight (ELBW; <1000 g) infants with WM abnormalities [7, 8]. Therefore, this study aimed to determine the diffusion tensor characteristics of WM regions associated with motor outcome among preterm infants with or without WM abnormalities and/or cerebral palsy (CP).…”
Section: Introductionmentioning
confidence: 99%